2009
DOI: 10.1002/cmdc.200900210
|View full text |Cite
|
Sign up to set email alerts
|

A Second Generation of Carbamate‐Based Fatty Acid Amide Hydrolase Inhibitors with Improved Activity in vivo

Abstract: The fatty acid ethanolamides are a class of signaling lipids that include agonists at cannabinoid and type-α peroxisome proliferator-activated receptors. In the brain, these compounds are primarily hydrolyzed by the intracellular serine enzyme fatty acid amide hydrolase (FAAH). Oaryl carbamate FAAH inhibitors such as URB597 are being evaluated clinically for the treatment of pain and anxiety, but interactions with carboxylesterases in liver might limit their usefulness. Here we explore two strategies aimed at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
74
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 42 publications
(68 reference statements)
1
74
0
Order By: Relevance
“…These findings are in agreement with those previously reported for mice (Clapper et al, 2009). Furthermore, concentrations of anandamide, PEA, and OEA, all of which are FAAH substrates (Cravatt et al, 1996), were significantly elevated in the midbrain of monkeys receiving URB597 or URB694, whereas levels of 2-AG, which is degraded by monoacylglycerol lipase (MGL), remained unaffected (Figure 1c-f; effect of treatment; anandamide: F 2, 11 = 61.99, po0.0001, PEA: F 2, 11 = 47.04, po0.0001, OEA: F 2, 11 = 72.56, po0.0001, 2-AG: F 2, 10 = 0.20, p = 0.82).…”
Section: Effects Of Urb597 and Urb694 On Faah Activity And Levels Of supporting
confidence: 94%
See 2 more Smart Citations
“…These findings are in agreement with those previously reported for mice (Clapper et al, 2009). Furthermore, concentrations of anandamide, PEA, and OEA, all of which are FAAH substrates (Cravatt et al, 1996), were significantly elevated in the midbrain of monkeys receiving URB597 or URB694, whereas levels of 2-AG, which is degraded by monoacylglycerol lipase (MGL), remained unaffected (Figure 1c-f; effect of treatment; anandamide: F 2, 11 = 61.99, po0.0001, PEA: F 2, 11 = 47.04, po0.0001, OEA: F 2, 11 = 72.56, po0.0001, 2-AG: F 2, 10 = 0.20, p = 0.82).…”
Section: Effects Of Urb597 and Urb694 On Faah Activity And Levels Of supporting
confidence: 94%
“…Prior work has shown that URB694 inhibits FAAH activity in the rat brain (Clapper et al, 2009), but the pharmacokinetic properties of this compound have not been reported. Because understanding these properties is relevant to interpretation of the effects of drugs on reward-related behaviors, which are strongly dependent on the kinetics of penetration into the brain, we administered URB694 (3 and 10 mg/kg, IP) to rats and measured circulating levels of the compound by LC/MS at various times (0-480 min) after injection.…”
Section: Pharmacokinetic Profile Of Urb694 In Ratsmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that the electronic distribution of the carbamate has a negligible effect on Ser241 carbamoylation, in spite of its profound importance for chemical and plasmatic stability of these compounds. 12 This can be understood as this TS structure is characterized by deprotonation of Ser241 (H 1 is found between O 1 and O 2 ), with the nucleophile O 1 still approaching the carbonyl carbon of the inhibitor ( Table 1).…”
mentioning
confidence: 99%
“…12 Structure-activity relationship (SAR) studies showed that conjugated, electron-donor groups on the biphenyl scaffold of URB524 (which increase electron density around the carbamate carbon) are associated with enhanced carbamate stability both in alkaline buffer and in rat plasma. 13 Conversely, these groups do not affect FAAH inhibitor potency in vitro.…”
mentioning
confidence: 99%